Gelation behavior and properties of lead zirconate titanate gel-cast under an electric field - Alkoy, Sedat; Kaya, M. Y. (Institute of Electrical and Electronics Engineers Inc., 2009)
Lead zirconate titanate (PZT) piezoelectric ceramics are fabricated by gelcasting method. The effect of gelling additives on the gelation behavior was investigated in details with a focus on the fine control of incubation time before gelling. Gelcasting was also tried under the application of an electric field up to 10 kV/cm to investigate its effect on the physical properties of the ceramics after sintering. Dense ceramics with electrical properties comparable to that of conventional dry pressed ones were obtained using the gelcasting method. Initial experiments on the application of electric field during gelation indicated formation of a thin porous layer on the surface of the ceramic but, otherwise, no significant effect on the properties. ©2009 IEEE. © 2020 Elsevier B.V., All rights reserved.
2009 IEEE International Ultrasonics Symposium, IUS 2009 -- Rome -- 80324
Keywords: Electrical properties; Gelcasting; Piezoelectric; PZT